Microarray-based prenatal diagnosis for the identification of fetal chromosome abnormalities. (July 2013) - Shaffer, Lisa G; Rosenfeld, Jill A
The goal of prenatal cytogenetic testing is to provide reassurance to the couple seeking testing for their pregnancy, identify chromosome abnormalities in the fetus, if present, and provide treatments and medical management for affected babies. Cytogenetic analysis of banded chromosomes has been the standard for identifying chromosome abnormalities in the fetus for over 40 years. With chromosome analysis, whole chromosome aneuploidies and large structural rearrangements can be identified. The sequencing of the human genome has provided the resources to develop molecular tools that allow higher resolution observations of human chromosomes. The future holds the promise of sequencing that may identify chromosomal imbalances and deleterious single nucleotide variants. This review will focus on the use of genomic microarrays for the testing and identification of chromosome anomalies in prenatal diagnosis and will discuss the future directions of fetal testing.